Bilateral hippocampal increase following first-episode psychosis is associated with good clinical, functional and cognitive outcomes. Issue 6 (April 2014) - Lappin, J. M.; Morgan, C.; Chalavi, S.; Morgan, K. D.; Reinders, A. A. T. S.; Fearon, P.; Heslin, M.; Zanelli, J.; Jones, P. B.; Murray, R. M.; Dazzan, P.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Hippocampal pathology has been proposed to underlie clinical, functional and cognitive impairments in schizophrenia. The hippocampus is a highly plastic brain region; examining change in volume, or change bilaterally, over time, can advance understanding of the substrate of recovery in psychosis. Method Magnetic resonance imaging and outcome data were collected at baseline and 6-year follow-up in 42 first-episode psychosis subjects and 32 matched controls, to investigate whether poorer outcomes are associated with loss of global matter and hippocampal volumes. Bilateral hippocampal increase (BHI) over time, as a marker of hippocampal plasticity was hypothesized to be associated with better outcomes. Regression analyses were performed on: (i) clinical and functional outcomes with grey matter volume change and BHI as predictor variables; and (ii) cognitive outcome with BHI as predictor. Results BHI was present in 29% of psychosis participants. There was no significant grey matter loss over time in either patient or control groups. Less severe illness course and lesser symptom severity were associated with BHI, but not with grey matter change. Employment and global function were associated with BHI and with less grey matter loss. Superior delayed verbal recall was also associated with BHI. Conclusions BHI occurs in a minority of patients following their first psychotic episode and is associated with good outcome across clinical, functional and cognitive domains.